AUGMENTED REALITY-ENHANCED EXPERIENTIAL LEARNING AND ITS IMPACT ON NUMERACY SKILL DEVELOPMENT IN EARLY CHILDHOOD - Ruqoyyah Fitri; Firasya Nurin Khairina (Program Studi PGSD Universitas Flores, 2026)
development. However, conventional learning methods are often less engaging and effective. Experiential learning assisted by Augmented Reality (AR) offers an interactive approach that can increase children's involvement in the numeracy learning process. This study aims to analyse the effect of experiential learning assisted by AR media on the numeracy skills of children aged 4 to 5 years. The research used a quasi-experimental method with a pretest-posttest control group design. The sample consisted of 30 children divided into an experimental group (AR-assisted learning) and a control group (conventional method). The research instruments included a numeracy test and an observation of a learning activity. Data were analysed using a parametric statistical test (t-test). The results showed that the experimental group experienced a significant increase in numeracy skills (p< 0.05) compared to the control group. AR media proved effective in improving the understanding of number concepts, sequencing, and basic operations through an immersive and fun learning experience.